2016
DOI: 10.1016/j.jclepro.2015.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Ex-ante Life Cycle Assessment approach developed for a case study on bio-based polybutylene succinate

Abstract: International audienceThe evaluation of the environmental impact of an innovative material at an early stage of development is of fundamental importance during the design phase of a product. In this regard, a full-fledged Life Cycle Assessment presents some major limitations: it can be performed mainly as an ex-post analysis, and it does not account for the intrinsic properties of the material. The growing need to compare the properties of new materials with those of industrially optimized ones poses further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…The topics of food production (n = 4), mobility (n = 2), and biomass production (n = 1) are analyzed as well. Most authors concluded that applying prospective LCA is useful, leads to new insights during the development of new technologies, and can support policymakers in their work [25,26,32,[34][35][36][37]. Zimmermann et al [27] expand this argument in concluding that prospective LCAs lead to a more robust analysis than traditional static LCAs.…”
Section: Resultsmentioning
confidence: 99%
“…The topics of food production (n = 4), mobility (n = 2), and biomass production (n = 1) are analyzed as well. Most authors concluded that applying prospective LCA is useful, leads to new insights during the development of new technologies, and can support policymakers in their work [25,26,32,[34][35][36][37]. Zimmermann et al [27] expand this argument in concluding that prospective LCAs lead to a more robust analysis than traditional static LCAs.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the environmental impacts of such a new bio-based chemical products, the life cycle assessment (LCA) represents an effective analytical tool [13,17,18]. All the direct and indirect environmental impacts associated with the product, process or activity are included in the assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Life Cycle Assessment (LCA) has been used as a tool to quantify environmental impacts associated with bioplastics throughout its life cycle. Some studies focused on 'cradle-to-factory gate' [10][11][12][13][14][15] LCA or from the feedstock cultivation and harvesting to bioplastic resin. However, some researchers studied the impacts from acquisition of feedstock to end-of-life (EOL) or 'cradle-to-grave' approach [14,16,17].…”
Section: Introductionmentioning
confidence: 99%